2018
DOI: 10.3389/fnins.2018.00713
|View full text |Cite
|
Sign up to set email alerts
|

Nonapeptide Receptor Distributions in Promising Avian Models for the Neuroecology of Flocking

Abstract: Collective behaviors, including flocking and group vocalizing, are readily observable across a diversity of free-living avian populations, yet we know little about how neural and ecological factors interactively regulate these behaviors. Because of their involvement in mediating a variety of social behaviors, including avian flocking, nonapeptides are likely mediators of collective behaviors. To advance the neuroecological study of collective behaviors in birds, we sought to map the neuroanatomical distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…Leung et al (2009; reported that RA capsular labeling was absent in adult zebra finches; instead, the arcopallium labeling seen in adults resembled what we saw here in P75-95 juveniles. Notably, the distinctive 125 I-OVTA labeling in capsular RA that we see here in young zebra finches was previously described in adults of several seasonally breeding species, including canaries (Voorhuis et al, 1990), house sparrows (Ondrasek et al, 2018), European starlings (Ondrasek et al, 2018), dark-eyed juncos (Wilson et al, 2016), and white-throated sparrows (Leung et al, 2009). In seasonal species, song can become highly variable, not unlike plastic song, Fig.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Leung et al (2009; reported that RA capsular labeling was absent in adult zebra finches; instead, the arcopallium labeling seen in adults resembled what we saw here in P75-95 juveniles. Notably, the distinctive 125 I-OVTA labeling in capsular RA that we see here in young zebra finches was previously described in adults of several seasonally breeding species, including canaries (Voorhuis et al, 1990), house sparrows (Ondrasek et al, 2018), European starlings (Ondrasek et al, 2018), dark-eyed juncos (Wilson et al, 2016), and white-throated sparrows (Leung et al, 2009). In seasonal species, song can become highly variable, not unlike plastic song, Fig.…”
Section: Discussionsupporting
confidence: 69%
“…Although the ligand is highly selective for OTR in rodents, it was more recently shown to bind to both OTR and vasopressin 1a receptors (V1aR) in primates (see Freeman & Young 2016). Its relative affinity for avian nonapeptide receptors has not been thoroughly investigated (but see Leung et al, 2009;Ondrasek et al, 2018;Voorhuis et al, 1990). Songbirds have at least three different nonapeptide receptors that are expressed in brain: OTR, V1aR, and vasopressin 2 receptors (V2R) (Leung et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Four avian nonapeptide receptors are known, and the nomenclature of the corresponding mammalian receptors based on homology is listed in Table . Notably, telencephalic brain nuclei that show greater activation with exposure to predisposed stimuli have also been documented to have enriched expression of mRNAs for nonapeptide receptors in the white‐throated sparrow and zebra finch (Leung et al., ) as well as in the rock dove, European starling and house sparrows (Ondrasek, Freeman, Bales, & Calisi, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the domestic chick ( Gallus gallus), both the lateral septum and the avian partial homolog of the medial amygdala, the nucleus taeniae, are selectively responsive to features of predisposed stimuli (Lorenzi et al., ; Mayer, Rosa‐Salva, Loveland, & Vallortigara, ; Mayer, Rosa‐Salva, & Vallortigara, ) and these brain nuclei are known to express nonapeptide receptors in several species, including the chicken (Goodson, Schrock, Klatt, Kabelik, & Kingsbury, ; Leung et al., ; Ondrasek et al., ; Selvam, Jurkevich, & Kuenzel, ; Wilson et al., ). Therefore, it is reasonable to suggest that nonapeptide signalling in these brain nuclei may also be important for initiating the process of imprinting.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of nonapeptide receptors by endogenous mesotocin also promotes social behaviour (preferences for larger groups) and the preference for familiar social partners in the gregarious zebra finch . Antagonism of oxytocin receptors also reduces the preference for larger groups in finches .…”
Section: Birdsmentioning
confidence: 99%